IMPLEMENTASI KEBIJAKAN PEMBAHASAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH PADA DEWAN PERWAKILAN RAKYAT DAERAH KOTA PALU - Moh Irsyad Pratama; Moh Irfan Mufti; M Nur Alamsyah; Mustainah M (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This study aims to find out and analyze how the implementation of the regional revenue and expenditure budget discussion policy at the Palu City Regional People's Representative Council. This research is a qualitative study with descriptive methods and an indukative approach that uses the policy implementation model from Charles O. Jones by paying attention to 3 (three) indicators, namely organization, interpretation and implementation. In collecting data, researchers used data collection techniques by means of observation, interviews and documentation, while data analysis techniques by condensing data and presenting it in the form of narrative text so that final conclusions can then be drawn in this research. Through this research it can be concluded that the implementation of the policy of discussing the regional budget revenue and expenditure at the Regional People's Representative Council of Palu City has been running in accordance with the provisions in the applicable laws and regulations both from the stages and schedules given but the discussion still seems rushed because it is always at the end of the time regulated in the provisions so that the discussion is still not optimal.